Optimal design of geometrically non- linear laminated structures - Moita, José Mateus Simões (2009)
The mechanical properties of a laminate are strongly dependent of the fiber directions and because of that the lamenate should be designed to meet the specific requirements of each particular application in order to obtain the maximum advantages.